THE EFFECT OF SNAKE AND LADDER GAME ON STUDENT LEARNING OUTCOMES IN STUDYING OF ISLAMIC HISTORY “FATHU MECCA” AT THE ELEMENTARY SCHOOL MUHAMMADIYAH, NORTH SUMATERA, INDONESIA - Rora Rizky Wandini; Emeliya Sukma Dara Damanik; Sholihatul Hamidah Daulay; Wahyu Iskandar (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
This study examines the effect of the snake and ladder game on Islamic history Fathu Mecca learning outcomes based on observations at the SD Muhammadiyah in Indonesia. Students have been shown to acquire standard competency through the study of Islamic history. This course is very important to build a strong Muslim identity, especially in Islamic School Muhammadiyah. Meanwhile, the snake and ladder game has been used by several educators in the teaching and learning process. This game positively influences students’ learning outcomes. Therefore, the authors developed and integrated Islamic history into the snake and ladder game board. This research was a quantitative study conducted on 60 fifth-grade students divided into experiment and control classes. Furthermore, the data were collected using observation, interview, and t-test hypotheses. The results showed that the snake and ladder game positively affects students’ learning outcomes in studying Islamic history. Based on the result, this game provides opportunities for students to explore, identify, practice, and understand concepts. The teachers are expected to encourage students to develop skills for discovering knowledge through an inspiring and fun learning atmosphere.